Effectiveness of Fear, Anxiety and Depression on Functional Ability in Patients with Spinal Cord Injury - Asthana, Sumit; Rizvi, Arif; Rasheed, Rutba (Journal of Biomedical and Pharmaceutical Research, 2024)
Introduction: The spinal cord is the major conduit through which motor and sensory information travels between brain and body. Spinal cord injury (SCI) affects conduction of sensory and motor signals across the site of lesion19. SCI is a low- incidence, high cost disability requiring tremendous change in an individual’s life-style25. The consequence of SCI is usually permanent paralysis of voluntary muscles below the lesion, reduced mobility, impairment of social and vocational activities, with a negative impact on body systems such as respiratory, cardiovascular, urinary, gastrointestinal, reproductive and sensory.19 When a sudden-onset spinal cord injury (SCI) occurs, there are often multiple levels of trauma to address, including acute medical issues, new functional limitations, psychological reactions (e.g. anger, anxiety, depression, and denial about the permanency of the condition)that persists for months or years , distressing memories related to the traumatic event causing the SCI, and possible role changes caused by the SCI. Growing evidence suggests psychological factors such as anxiety, fear, and depression may also relate to physical function in patients with SCI. The psychological variables of fear, anxiety, and depression can be associated with each other, and therefore it may be possible that they could interact to have a greater effect on physical function.3 Objective: To study effectivness of fear, anxiety and depression on functional ability in patients with spinal cord injury Research Design: Correlational design Methodology: On the first visit, a detailed examination of subjects was done and the subjects found eligible on the basis of inclusion and exclusion criteria, were explained about the study and were requested to sign the informed consent for seeking their willingness to participate in the study.Out of 153 subjects of SCI who volunteered for this study, 100 subjects were included in the study after they met the inclusion criteria. Subjects were assessed for various psychological variants via Depression, Anxiety and Fear- avoidance beliefs. Result: Depression was the most highly associated variable for physical function in Regression model meaning that depression highly affects physical performance in Spinal Cord Injury Patient. The results also revealed significant associations between each psychological variable and all the measures of function. High levels of fear avoidance beliefs, anxiety and depression were associated with reduced self- reported measures Conclusion: An important aspect of this study is that it has specifically examined the effect of some elements of psychological variants (depression, anxiety and fear avoidance beliefs) on physical function in chronic SCI patients. Higher psychological variants are significantly and independently related to poorer physical function in bivariate correlation model. In addition, depression has been found to be the strongest factor among all the psychological variants that have a great association with performance based measure of physical function. Keywords- SCI, anxiety, depression, psychological variables, rehabilitation